2018
DOI: 10.1002/mp.13030
|View full text |Cite
|
Sign up to set email alerts
|

Direction modulated brachytherapy (DMBT) tandem applicator for cervical cancer treatment: Choosing the optimal shielding material

Abstract: The Ir, Pt, Os, Au, Re, and W shielding materials, respectively, in descending order, lead to better OAR sparing than the DMBT(W')&R plans. However, the amount of improvement is limited and clinically insignificant. This finding suggests that the initial W' shield remains a suitable choice given the proven MR compatibility, for use in MR-guided adaptive brachytherapy of cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…1K). [27][28][29][30][31][32][33][34] As expected, static-shield IMBT methods did increase delivery times by 25%-319% relative to those of conventional BT plans. 21,25,28 However, these increases still yielded clinically feasible absolute delivery times of w20 minutes.…”
Section: Static-shielded Applicatorssupporting
confidence: 68%
See 3 more Smart Citations
“…1K). [27][28][29][30][31][32][33][34] As expected, static-shield IMBT methods did increase delivery times by 25%-319% relative to those of conventional BT plans. 21,25,28 However, these increases still yielded clinically feasible absolute delivery times of w20 minutes.…”
Section: Static-shielded Applicatorssupporting
confidence: 68%
“…Two studies for conceptual IMBT were reported with no specific applicator design. 81,82 Twenty-five studies were on clinically implemented IMBT techniques, 6,7,23,26,35,36,38-43,47-49,53,56,58,63,83-88 13 included a prototype of the applicator, 3,4,18,19,27,28,[31][32][33][34]66,73,78 and most of the other studies using simulated IMBT plans on real patients' simulation scans or dosimetric evaluations.…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the dosimetric advantages of IC/IS over IC, IC/IS is more challenging, 7 invasive, 8,9 and time‐consuming 3 to deliver than IC. Multiple intracavitary HDR‐BT approaches using partial source shielding within the tandem applicator have been proposed to reduce or eliminate the need for interstitial HDR‐BT in cervical cancer patients, including rotating shield brachytherapy (RSBT) 10–14 and direction‐modulated brachytherapy (DMBT) 15–21 . Rotating shield brachytherapy relies on rotational movement of high‐density shields to modulate dose rate and direct radiation away from organs‐at‐risk (OARs) and into the HR‐CTV, which can increase dose delivered to the HR‐CTV without violating OAR dose constraints.…”
Section: Introductionmentioning
confidence: 99%